EMI challenges in modern power electronic-based converters: recent advances and mitigation techniques - Yuan, Liang; Zhang, Jian; Liang, Zheng; Hu, Mingxin; Chen, Genhua; Lu, Wei (Frontiers in Electronics, 2023)
The utilization of power electronics-based converters is gaining momentum across a wide spectrum of industries. However, modern power electronics converters operate at higher frequencies compared to conventional power electronics converters, which can lead to larger rates of change in voltage and current during phase switching, and thus potentially produce more severe conducted and radiated electromagnetic interference (EMI). Their electromagnetic compatibility (EMC) has become a critical research topic, and the EMI in high-frequency power electronics-based converters is more complex than that in conventional converters. This review presents a comprehensive survey of recent advancements EMI design and analysis of modern power electronics-based converters, focusing on the sources and mechanisms of both conducted and radiated EMI, and mitigating techniques. The review also covers the impact of topology optimization, control strategy design, and packaging design on EMC performance. Addressing emerging EMI issues in modern power electronics devices-based converters is essential for ensuring safe and reliable operation. Through strategic design optimization and the implementation of EMI mitigation strategies, modern converters can be seamlessly integrated into diverse applications, offering improved EMI performance as a hallmark of their versatility.